Lamb feeding experiments - Menzies, C.S.; Erhart, A.B. (Kansas Agricultural Experiment Station, 2011)
Lambs used were finewool wethers purchased from the Zuni Indian Reservation near Gallup, New Mexico. Average purchase weight of 699 head was 63.8 lbs.; cost was $23.50 per cwt. plus 15 cents per head commission. Lambs were trucked to Garden City, arriving October 15. Shrinkage during shipment was 5.8 lbs. (9.10%). Chopped grain sorghum stubble and alfalfa hay were fed until lambs went on test.
Keywords: Lamb; Silage; Sorghum grain; Growth